Observations on the health of infants at a time of rapid societal change: a longitudinal study from birth to fifteen months in Abu Dhabi - Hazel Gardner; Katherine Green; Andrew S. Gardner; Donna Geddes (BMC, 2018)
Abstract Background Rapid economic and cultural transition in the United Arab Emirates has been accompanied by a rise in chronic disease. Early childhood is known to affect health outcomes in adulthood. This prospective longitudinal study examined the general health of Emirati infants born in a government maternity hospital in the Emirate of Abu Dhabi in October 2002. Methods One hundred twenty-five women, who had recently given birth, were interviewed as part of a larger study encompassing a wide range of cultural, social, and behavioural aspects of health. They were then re-interviewed at three (n = 94), six (n = 59) and 15 months postpartum (n = 52). Data are presented using univariate statistics. Results In this study seven infants (6%) were born prematurely and four infants (3%) were classified as small for gestational age, while 11 (9%) of the infants weighed less than 2500 g. Low birth weight infants (LBW) were significantly more likely to require treatment in the neonatal intensive care unit (OR = 30.83, p = 0.00). Iron supplementation during pregnancy was associated with fewer underweight infants (OR = 3.92, p = 0.042). No associations were found between infant birth weight and maternal age, age at marriage, consanguinity, education level, current maternal employment, parity, pre-existing anaemia or anaemia in pregnancy, diabetes, folic acid intake, multivitamin intake or infant gender. Maternally-reported infant health issues, vaccination, medication, breast-feeding and infant nutrition, and use of secure car seats are also reported. Conclusions The health of infants at birth in this UAE sample showed improvements compared to previous studies. The proportion of LBW infants is decreasing and continuing improvements in health care in the UAE are having a positive impact on infant health.